Research progress of umbilical cord mesenchymal stem cells in repairing skin wounds - WU Wen-zhe, SUN Jian-wei, FU Chang-xiu, HUANG Li-chen-lu, ZHENG Yong-qin, HE Jun-dong (Jichu yixue yu linchuang, 2022)
Umbilical cord mesenchymal stem cells (UC-MSCs) are a kind of adult stem cells with low immunogenicity, which are easy to collect and to expand in vitro. UC-MSCs can regulate wound inflammation, promote angiogenesis and cell proliferation, inhibit scar formation and induce the formation of skin appendages. UC-MSCs combined with other drugs can promote the adhesion, survival, migration and proliferation of UC-MSCs.